THE ROLE OF SOCIAL FACTORS IN THE FORMATION OF THE IMAGE OF "YOUTH" - Mamatmurodova Sohiba Muhammad qizi (Western European Studies, 2025)
This article analyzes the role of social factors in the formation of the image of youth. Based on Uzbek folk proverbs and phraseological units, the social, spiritual and cultural aspects of youth are highlighted. It is shown that the upbringing of youth, their desire for knowledge, morality and their place in society are closely related to social factors.
Keywords: Youth; image; social factor